THE INFLUENCE OF THE NATURAL EXPLORING METHOD ON STUDENT LEARNING OUTCOMES IN CLASS IV SCIENCE SUBJECTS AT MUHAMMADIYAH 11 MEDAN PRIMARY SCHOOL - Rahayu, Enny; Sitepu, Melyani Sari; Rahma, Anisa (Proceeding International Seminar of Islamic Studies, 2024)
This research is motivated by the low learning outcomes of students in science subjects because teachers still use the lecture method. This research aims to determine the effect of the natural exploration method on student learning outcomes in science subjects. The method used in this research is a quasi-experimental research method with a quantitative approach. Based on the results of the data analysis carried out, it was found that the average learning outcome for control class students using conventional methods in the pret-test was 66.59 and the post-test was 77.27. And the average learning outcomes of experimental class students in the pret-test was 73.86 and the post-test was 82.05. This shows that the average result in the experimental class (after using the environmental exploration method) was higher than the control class (conventional method). Meanwhile, the researcher carried out the analysis by testing the hypothesis, namely using the t-test to determine each variables have an influence or not, namely variables X and Y. The analysis results obtained show that the method of exploring the surrounding nature has a significant value of 0.022. So it can be concluded that if the significance value is 0.022 0.05, then Ha is accepted or there is an influence of the natural exploration method on student learning outcomes in science subjects.